2012
DOI: 10.1002/path.4057
|View full text |Cite
|
Sign up to set email alerts
|

Impaired decidual natural killer cell regulation of vascular remodelling in early human pregnancies with high uterine artery resistance

Abstract: During human pregnancy, natural killer (NK) cells accumulate in the maternal decidua, but their specific roles remain to be determined. Decidual NK (dNK) cells are present during trophoblast invasion and uterine spiral artery remodelling. These events are crucial for successful placentation and the provision of an adequate blood supply to the developing fetus. Remodelling of spiral arteries is impaired in the dangerous pregnancy complication pre-eclampsia. We studied dNK cells isolated from pregnancies at 9–14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 50 publications
2
127
0
1
Order By: Relevance
“…Our data clearly demonstrated that the fetal levels and genotype of Adm were the critical determinants of its function at tional differences between placentas of humans and mice (44)(45)(46), the reduction in fetal vascular branching, failed SA remodeling, and lack of SA reendothelialization we describe here have long been associated with preeclampsia in humans (47). More recently, additional studies demonstrating deregulation of uNK cells and the levels of placental chemokines and cytokines have also been appreciated in human preeclampsia (20,22). Finally, some of the most clinically relevant breakthroughs in recent years have been discoveries of numerous angiogenic factors and their soluble receptors as predictive biomarkers of preeclampsia, including soluble Fms-like tyrosine kinase 1 (sFlt1) and soluble endoglin (sEng) (48).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our data clearly demonstrated that the fetal levels and genotype of Adm were the critical determinants of its function at tional differences between placentas of humans and mice (44)(45)(46), the reduction in fetal vascular branching, failed SA remodeling, and lack of SA reendothelialization we describe here have long been associated with preeclampsia in humans (47). More recently, additional studies demonstrating deregulation of uNK cells and the levels of placental chemokines and cytokines have also been appreciated in human preeclampsia (20,22). Finally, some of the most clinically relevant breakthroughs in recent years have been discoveries of numerous angiogenic factors and their soluble receptors as predictive biomarkers of preeclampsia, including soluble Fms-like tyrosine kinase 1 (sFlt1) and soluble endoglin (sEng) (48).…”
Section: Discussionsupporting
confidence: 58%
“…uNK cells secrete a wide variety of growth factors, chemokines, cytokines, and MMPs (4) and thus represent a major constituent of the innate immune milieu of the placenta. Several recent studies have begun to reveal important pathophysiological roles for uNK cells in human pregnancy (19)(20)(21)(22). However, much remains unknown about the precise molecular interactions between fetal trophoblast cells and uNK cells in the placenta.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] We investigated whether sofalcone can reduce TNF-α-induced endothelial dysfunction by examining the degree of monocyte adhesion to endothelial cells stimulated with TNF-α (Figure 4). TNF-α-treated HUVECs significantly increased THP-1 monocyte adhesion to HUVECs compared with the control (n=3; P<0.01).…”
Section: Sofalcone Ameliorates Tnf-α-induced Endothelial Dysfunctionmentioning
confidence: 99%
“…For instance, they have been shown to be closely associated with remodeling vessels (Smith et al, 2009;Hazan et al, 2010), to promote trophoblast invasion (Hanna et al, 2006;De Oliveira et al, 2010;Fraser et al, 2012) and to stimulate vascular remodeling by the production of angiogenic factors (Hanna et al, 2006;Lash et al, 2006;Kalkunte et al, 2009). The interaction of activating NK cell receptors with MHC I molecules on trophoblast cells seems to promote both chemotactic and angiogenic factors (Hanna et al, 2006), suggesting that a moderate level of activation is necessary for proper trophoblast invasion and spiral artery remodeling.…”
Section: Decidual Nk Cellsmentioning
confidence: 99%
“…Another method may be the use of uterine artery Doppler ultrasound to define first trimester pregnancies with normal or high resistance indices. This measurement reflects the level of spiral artery remodeling and thus the risk of developing complications associated with impaired vascular remodeling, such as preeclampsia (Fraser et al, 2012). However, only an approximation of the risk is obtained and only to a certain group of complications.…”
Section: First Trimester Samples As a Model Of Healthy Pregnancymentioning
confidence: 99%